APOBEC3C‐mediated NF‐κB activation enhances clear cell renal cell carcinoma progression - Hase, Nora; Misiak, Danny; Taubert, Helge; Hüttelmaier, Stefan; Gekle, Michael; Köhn, Marcel (Molecular oncology, 2025)
Renowned as the predominant form of kidney cancer, clear cell renal cell carcinoma (ccRCC) exhibits susceptibility to immunotherapies due to its specific expression profile as well as notable immune cell infiltration. Despite this, effectively treating metastatic ccRCC remains a significant challenge, necessitating a more profound comprehension of the underlying molecular mechanisms governing its progression. Here, we unveil that the enhanced expression of the RNA‐binding protein DNA dC → dU‐editing enzyme APOBEC‐3C (APOBEC3C; also known as A3C) in ccRCC tissue and ccRCC‐derived cell lines serves as a catalyst for tumor growth by amplifying nuclear factor‐kappa B (NF‐κB) activity. By employing RNA‐sequencing and cell‐based assays in ccRCC‐derived cell lines, we determined that A3C is a stress‐responsive factor and crucial for cell survival. Furthermore, we identified that A3C binds and potentially stabilizes messenger RNAs (mRNAs) encoding positive regulators of the NF‐κB pathway. Upon A3C depletion, essential subunits of the NF‐κB family are abnormally restrained in the cytoplasm, leading to deregulation of NF‐κB target genes. Our study illuminates the pivotal role of A3C in promoting ccRCC tumor development, positioning it as a prospective target for future therapeutic strategies. The authors discovered that expression of the RNA‐binding protein APOBEC3C (A3C) promotes clear cell renal cell carcinoma (ccRCC) growth by amplifying nuclear factor‐kappa B (NF‐κB) activity. A3C‐bound mRNAs of NF‐κB regulators are stabilized, which promotes NF‐κB‐subunit shuttling and transcriptional activity. This study highlights A3C's role in enhancing ccRCC progression, positioning it as a target for therapeutic strategies.